Crystal structure of η′-Fe3Al8; low-temperature phase of η-Fe2Al5 accompanied by an ordered arrangement of Al atoms of full occupancy in the c-axis chain sites. (1st May 2017) - Okamoto, Norihiko L.; Okumura, Jumpei; Higashi, Masaya; Inui, Haruyuki
Abstract: The low-temperature phase of η-Fe2 Al5 has been identified experimentally for the first time and the crystal structure of the low-temperature phase (designated as η′) has been refined by scanning transmission electron microscopy, combined with first-principles calculations. The low-temperature η′ phase has a tripled superlattice structure based on the orthorhombic η-Fe2 Al5 (space group Cmcm ), in which Al atoms occupy two ninths of the partially occupied Al sites (Al2 and Al3) in a chain along the c -axis of the orthorhombic parent lattice in an ordered manner, giving rise to the monoclinic space group C 2/ c, the stoichiometric composition Fe3 Al8 (Al-27.3 at.%Fe), and the Pearson symbol mC 44. The partially occupied Al sites along the c -axis of the orthorhombic parent lattice are converted to the Al site (Al3″ site) of full occupancy in the monoclinic superlattice of the η′-Fe3 Al8 . The η-η′ phase transformation temperature decreases from between 350 and 400 °C at the composition of Al-26.7 at.%Fe to between 300 and 350 °C at compositions in the range of Al-27.3 to 28.6 at.%Fe, indicating that the η′ phase exists primarily at the Fe-lean side of the solid-solubility region of the η-Fe2 Al5 phase. Graphical abstract: Image